Perspektiewe op erotiek en seksualiteit in die ou Nabye Ooste - Human, Dirk J. (Verbum et ecclesia, 2006)
Sexuality and erotism form an integral part of life. Both these aspects mediate life fulfilling experiences of love. As part of the creation reality sexuality effects a positive power of life. Evidence from the ancient Near East, especially from Egypt, Canaan and Mesopotamia, confirms human’s facinasion for and participation in sexual behaviour. In the sexual experience the ‘I’ transcends the borders of the ‘self’. Whether the gods or humans are engaged in this act of heavenly ecstacy, it is evident that life’s meaning is captured in this life enriching experience of power, vitality and joy.